GC-MS Analysis, Antibacterial Activity, and Brine Shrimp Lethality of Anacardium occidentale Linn - Shrestha, Ram Lal; Gautam, Shree Dhar; Maharjan, Binita (Journal of Nepal Chemical Society, 2017)
Available with full text.